ANALISIS PENERAPAN KONSEP ECO-AIRPORT DENGAN MENGGUNAKAN METODE WILLINGNESS TO PAY DI BANDAR UDARA SYAMSUDIN NOOR BANJARMASIN KALIMANTAN SELATAN - Masrun Masrun; Muhammad Ruslan; Idiannor Mahyudin; Akhmad Rizali (Universitas Lambung Mangkurat, 2016)
landing aircraft must have a negative impact on the environment. therefore, necessary to assess the role of the community using the willingness to pay towards the implementation of eco-airport Syamsudin Noor Airport in Banjarmasin. The purpose of this study is to identify the condition of the airport now to the application of the concept of eco-airport underway, estimate what the public is willing to pay for environmental improvements, analyze the factors that affect the implementation of this concept. Selection of sample is purposive sampling. The study is divided into three groups of workers, the public and passengers. Workers 23 respondents, 12 respondents community, and passengers 57 respondents. Most respondents rate Syamsudin Noor Airport Banjarmasin quite clean, quite beautiful, quite noisy, quite, quite comfortable and does not know the concept of eco-airport. A total of 53 respondents are willing to pay an average willingness to pay Rp. 11.320,75 per person per flight. Variable cleanliness and beauty affect the value of willingness to pay by 10%.